Comparative characteristics of heavy metals content in the various types of mollusks’ tissues in Gomel water bodies and its adjacent territories - Makarenko, Andrei; Makarenko Тatiana (Journal of the Belarusian State University. Ecology, 2024)
The content and accumulation of some heavy metals in the soft tissues and shells of gastropods (Gastropoda: Limnaea stagnalis L. and Viviparus viviparus L.) and bivalves (Anodonta cygnea L. and Unio pictorum L.) were studied. Based on observations, a higher content of copper, chromium and nickel in the soft tissues of gastropods has been established. In chromium, the maximum content is typical for the tissues of the pond snail, while in the viviparus it is minimal. The content of lead, zinc, manganese and cobalt is higher in bivalves. In shellfish shells, the concentrations of lead, cobalt, chromium and zinc were below the detection limit. Copper is predominantly concentrated in the soft tissues of mollusks; nickel is evenly distributed between the soft tissues and shells. The manganese content in the tissues of bivalves exceeds the concentration in shells; the opposite trend is observed in gastropods. The presented series of accumulation of the studied metals for gastropods and bivalves have significant differences, which may be determined by the different availability of metals in the abiotic components of the reservoir for individuals of different classes of mollusks. The level of accumulation of individual metals in the tissues of gastropods in the control reservoir exceeded those values calculated for urban reservoirs, which was not observed in bivalves. Based on the data obtained, for a comprehensive assessment of water bodies in relation to determining the degree of contamination of abiotic components with heavy metals, we can recommend the viviparous as an indicator of copper and nickel, for determining contamination with zinc, manganese and cobalt - pearl barley, chromium - pond snail, lead - toothless. However, it is difficult to determine the degree of pollution of water bodies with heavy metals using only the soft tissues of mollusks and the values of the coefficients of metal accumulation in tissues based on bottom sediments; it is necessary to resort to special integral indicators of pollution.